Constraints Faced by Traditional Folk Media Artists and Development Functionaries for Rural Development in Rajasthan - Kumar, Praveen; Lenin, Venu (Indian Journal of Extension Education, 2021)
The study was concerned to analysethe constraints faced by traditional folk media artists and development functionaries in using traditional folk media for rural development in Jaipur and Jodhpur district of Rajasthan using nonparametric Kruskal-Wallis test during 2020. Various types of constraints catagorised into several sub constraints confronted by the folk media artists and development functionaries were technological, communication, management, social and financial constraints consisting of the overall mean as 3.63, 2.50, 2.48), 1.99 and 1.97, respectively. The Kruskal–Wallis statistic was applied to the combined scores ranking of the constraints was found to be 8.21 smaller than its tabulated value (9.48) at 5 per cent level of significance which indicated that all the constraints confronted by the folk artists and development functionaries during study did not differ significantly showing a similar pattern among the constraints.
Keywords: Constraints; Traditional folk media; kruskal- Wallis test; Development functionaries